Bioactive Lipids and Circulating Progenitor Cells in Patients with Cardiovascular Disease. (14th October 2016) - Hayek, Salim S.; Klyachkin, Yuri; Asfour, Ahmed; Ghasemzadeh, Nima; Awad, Mosaab; Hesaroieh, Iraj; Ahmed, Hina; Gray, Brandon; Kim, Jinhee; Waller, Edmund K.; Quyyumi, Arshed A.; Abdel-Latif, Ahmed K.
Abstract: Bone marrow-derived progenitor cells are mobilized into the peripheral blood after acute myocardial injury and in chronic ischemic heart disease. However, the mechanisms responsible for this mobilization are poorly understood. We examined the relationship between plasma levels of bioactive lipids and number of circulating progenitor cells (CPCs) in patients ( N = 437) undergoing elective or emergent cardiac catheterization. Plasma levels of sphingosine-1 phosphate (S1P) and ceramide-1 phosphate (C1P) were quantified using mass spectrometry. CPCs were assessed using flow cytometry. S1P levels correlated with the numbers of CD34+, CD34+/CD133+, and CD34+/CXCR4+ CPCs even after adjustment for potential confounding factors. However, no significant correlation was observed between C1P levels and CPC count. Plasma levels of S1P correlated with the number of CPCs in patients with coronary artery disease, suggesting an important mechanistic role for S1P in stem cell mobilization. The therapeutic effects of adjunctive S1P therapy to mobilize endogenous stem cells need to be investigated.